FREQUENCY OF IUGR IN PREGNANCY INDUCED HYPERTENSION - Humaira Zafar; Mubashara Naz (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To find out the frequency of Intrauterine fetal growth restriction (IUGR) in patients with pregnancy induced hypertension. Design: Observational study. Place and duration of study: This study was conducted in Gynaecology unit 1 at Allied Hospital Faisalabad from March 2005 to February 2006. Fifty patients with pregnancy induced hypertension presented to gynae unit 1 were enrolled using convenience sampling technique. Patients and methods: After informed consent and history these patients were examined. Other causes of IUGR were excluded. Per abdominal examination was done to assess Symphysis fundal height, lie, presenting part, amount of liquor and USG was done to assess BPD, FL, abdominal circumference, head circumference and amount of liquor. Fetal growth monitoring was done by measuring serial Symphysis fundal height (SFH) and serial ultrasound (USG) after every two weeks. Results: The frequency of IUGR in patients with PIH was found to be 28%. Conclusion: IUGR is a major neonatal health issue. A prevalence of IUGR in excess of 20% has been recommended as cutoff point for triggering public health action. The prevalence in Pakistan is 25%. Maternal factors have been found to have great impact on IUGR. Studying these factors can help in reducing the mortality and morbidity associated with IUGR by timely intervension